Interrelation of Neuropsychological and Personality Factors with the Choice of Strategies of Coercion or Nonviolence among Students of the Socionomic Sphere - Vladimir G. Maralov; Marina A. Kudaka; Olga V. Smirnova; Viacheslav A. Sitarov; Irina I. Koryagina; Larisa V. Romanyuk (National Research Mordova State University, 2022)
Introduction. The urgency of the problem is caused by the importance of formation of ability to non-violent interaction in students of socionomic (helping) sphere as the most important professional competence that assumes study of factors and conditions of its formation and development. The aim of the research is to identify the relationship between neuropsychological and personal factors with the choice of students ‒ future medical, psychological, pedagogical psychologists in the process of interaction strategies of coercion or nonviolence. Materials and Methods. The study involved students from a number of universities in the Russian Federation: Moscow, Cherepovets, Vologda region, Ivanovo, Ivanovo region. In total - 334 people. As a diagnostic tool, the authorʼs questionnaire was used to identify the positions of interaction among students, the Carver ‒ White questionnaire in the adaptation of G. G. Knyazev, the questionnaire for the diagnosis of five personality factors in the adaptation of L. F. Burlachuk and D. K. Korolev, the scale "Moral normativity" questionnaire "Adaptability" Maklakov - Chermyanin. Mathematical processing was carried out with the help of correlation analysis; Spearman ʼs rank correlation coefficient was also used. Results. It was established that the choice of coercion strategy by students in the process of interaction is associated with a high level of behavioral activation, low levels of benevolence, conscientiousness and moral normativity. The choice of manipulation strategy, in addition to this, is correlated with high neuroticism. Nonviolence is positively associated with benevolence, conscientiousness, and moral normativity, and negatively to neuroticism. Noninterference correlates negatively with the Behavioral Inhibition System and positively with the Behavioral Inhibition System, as well as with neuroticism, introversion and closeness to experience and low conscientiousness. Discussion and Conclusion. The obtained results make a certain contribution to understanding of the problem of the relationship between students' choice in the process of interaction of strategies of coercion or nonviolence with neuropsychological and personal factors, which makes it possible to develop special programs aimed simultaneously at teaching methods of nonviolent interaction, and at the development of certain personal qualities, taking into account individual severity. systems of activation and inhibition of behavior.